PENGARUH PENERAPAN METODE PENEMUAN TERBIMBING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Wulandari, Sri; Tampubolon, Budiman; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is to analyze the effect of to analyzing the inflience the application of guided discovery method on learning outcomes Math of fourth grade students of SDN 03 South Pontianak.The method used in this study is an experimental method to form the study was Quasi Experimental Design, with experimental design Nonequivalent Control Group Design. The population were all fourth grade students of SDN 03 South Pontianak. The sample in this research is class IV A (control) and IV D (experiment) SDN 03 Pontianak City numbering 62 people. Based on statistical calculations of the average final test experimental class average of 81,16 and learning results of final test control class 69,33 final test data of 3,388 and ttable 2,000, because t (3,388) > ttabel (2,000), so Ha is received. Thus, it can be concluded that there are significant implementation of guided discovery method to student learning outcomes in mathematics in the fourth grade SDN 03 South Pontianak. From the calculation of effect size (ES), obtained by ES of 0.82 (high category). This means the implementation of guided discovery method give high regard for students learning outcomes on learning Math in class IV Elementary School SDN 03 South Pontianak. Keywords : Guided Discovery Method, Learning Outcomes